Emotional overeating and eating motives during COVID-19 in Polish women: Intergroup comparison among participants in various body mass index categories - Adriana MODRZEJEWSKA; Justyna MODRZEJEWSKA; Kamila CZEPCZOR-BERNAT; Julia WYSZOMIRSKA (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2024)
Introduction: Taking into account the situation of the COVID-19 pandemic and the ac-companying lockdown resulting in increased negative emotions, it is interesting to learn about eating motives and behaviors and check their intensity. The aim of this study was to investigate the differences between Polish women in various body mass index categories in terms of eating motives and emotional overeating during the COVID-19 pandemic. Material and methods: This study sample comprised 1,447 women (Mage = 31.34 ± 11.05; MBMI = 23.79 ± 4.59). The research used the following tools: the Eating Motivation Survey, the Emotional Overeating Questionnaire, and socio-demographic questions. Results: Focusing on selected significant outcomes, women with obesity had a higher level of emotional overeating and affect regulation related-eating motive and a lower level of need & hunger- and health-related eating motives than women with normal body weight. Conclusions: In view of the results of this and other eating-behavior-related studies, it is worth considering the possibility of additional researches related to the COVID-19 pandemic and other crisis situations. Eating behaviors are an important aspect of maintaining proper mental and physical health of people, so it is worth remembering that public healthcare professionals (such as psychologists, nutritionists, and primary care physicians) can effectively help reduce incorrect eating behaviors.